The etiology of periodontal disease in obese people and post bariatric surgery (Research, Society and Development, 2021)
Periodontal disease (PD) is an inflammation that affects the structures that protect, support or sustain a tooth, and can be strongly associated with obesity and patients undergoing bariatric surgery. These patients are part of the susceptible groups to the development of this type of disease, and are therefore considered risk factors. The aim of this article is to address the association of periodontal disease in obese patients and in individuals undergoing bariatric surgery, its causes and how this disease is manifested in these two major groups. This is an integrative review, and articles from the last 10 years related to the subject were searched in PubMed databases, with the keywords: "periodontal disease", "obesity", "bariatric surgery".  Seventeen articles were selected from the searches and by applying the inclusion and exclusion criteria. In view of the above, it is noted the need for the approach of a dental surgeon to perform periodontal assessment, prevention, treatment and control both preoperatively, transoperatively and postoperatively. The team that cares for patients undergoing weight loss surgery should be multidisciplinary so that such care is done properly and completely, taking into account the importance of maintaining oral health throughout the weight loss process and re-establishing the systemic health of these patients.